Cómo evitar el plagio académico Guía práctica para estudiantes y docentes - Hurtado Tiza, David Raul (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
This book "How to Avoid Academic Plagiarism: A Practical Guide for Students and Teachers" is designed to help students and teachers understand and avoid academic plagiarism. It presents strategies for proper citing and referencing, discusses best practices to avoid accidental plagiarism, explains the different ways plagiarism can occur, and presents plagiarism detection tools that are available to students and teachers. The objective was to provide a practical and accessible guide for students and teachers who wish to avoid academic plagiarism. Strategies that can be implemented by students and teachers alike are discussed, and useful tips are provided to address the problem of academic plagiarism in the classroom. By using the strategies presented in this book, students and teachers can create high-quality academic work that reflects their knowledge and skills.